Evaluation of Retrofit Approaches for Two Social Housing Tower Blocks in Portsmouth, UK. Issue 1 (26th January 2018) - Aragon, Victoria; Teli, Despoina; James, Patrick
The UK aims to reduce its carbon emissions focusing on the renovation of its existing building stock, particularly on the residential sector. Within this group, social housing is an excellent candidate for retrofits, but faces specific challenges. The cases presented in this study are social housing tower blocks in the City of Portsmouth, which are destined to be retrofitted but present particularities within its architecture, heating system, and occupants' behaviour and comfort perception. This study presents an analysis of the thermal performance of these buildings after different retrofit intervention scenarios were undertaken to evaluate heating loads, comfort and overheating. A dynamic simulation model was developed using the software TRNSYS and included performance evaluation under future climate change scenarios. Firstly, the buildings were modelled under different occupier energy profiles and the results in all cases, show that the physical properties of the building lead to a high level of energy consumption and discomfort. Moreover, the simulation of possible retrofits demonstrated that improving the building envelope to meet 2010 Building Regulations or stricter standards would result in a decrease of more than 80% of the heating load but would result in overheating if no adequate shading is installed. The analysis indicates that the best performing retrofit corresponded to a mixed system of MHRV for heating and natural ventilation during the summer. The paper concludes that (a) existing buildings are inefficient and a retrofit would result in a complete change in their energy performance and (b) that a thorough economic appraisal is required to select the best environmentally and economically viable interventions.